Self-Employment and Support for the Dutch Pension Reform - Karpowicz, Izabela (IMF Working Papers; Working Paper ;, 2019)
The Netherlands' pension system is characterized by high participation rates, adequate retirement income, strong capitalization and sustainability. Pressure points are arising, however, due to population aging and untransparent intergenerational transfers inherent in the system. Moreover, the Dutch pension system needs to adapt to the changing labor market landscape with an increasing share of workers in self-employment not covered by any pension arrangement. The government has proposed replacing collective defined-benefits schemes with personal accounts, and abolishing uniform premia and constant accrual rates. The micro-data analysis shows that allowing greater risk-taking and freedom of choice in managing pension savings could crowd self-employed into pension schemes.